Utility of nucleated RBCs in critical care patients in a tertiary care centre - Mitila, T.; Vinothkumar, B.; Balaji, S.; Yogalakshmai, E. (International Journal of Research in Medical Sciences, 2023)
Background: In healthy adults and older children, NRBCs are normally found only in the blood-building bone marrow where they mature. Their appearance in peripheral blood points to extramedullary erythropoiesis or disruption of the blood-bone marrow barrier. Aim of current study was to evaluate and compare the prognostic significance of NRBCs in the peripheral blood of intensive care patients (ICU) and non-intensive care patients (non-ICI) and to assess the morbidity and mortality risk associated with NRBCs among ICU and non-ICU patients. Methods: Relevant clinical details and investigations were collected from the Haematology nominal Register of the Department of Pathology, Saveetha Medical College. Blood samples were routinely drawn in the morning. The presence of NRBCs in the peripheral blood was detected with the help of an automated analyser (Sysmex XN 1000) and confirmed by a peripheral smear. Results: Among the NRBC-positive study population, mortality rate was 28% and was associated with ICU admission status, and death was predominantly due to cardiovascular causes. The highest NRBC value during the period of admission was significantly associated with deceased patients and ICU patients (p values of <0.001 and 0.002 respectively). The Pearson correlation of NRBC shows a significant positive correlation with serum creatinine and a negative correlation with platelets. Conclusions: The presence of NRBCs in the peripheral blood of critically ill adults is a significant prognostic marker of morbidity and mortality, laying down the emphasis on daily screening of peripheral smears for NRBCs.